1992
DOI: 10.1002/1097-0142(19920401)69:7<1750::aid-cncr2820690717>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic predictors of the behavior of surgically treated stage IB squamous cell carcinoma of the cervix a gynecologic oncology group study

Abstract: Disagreement persists about the superiority of Reagan and Ng's method over that of Broders' for the histologic grading of squamous carcinoma of the cervix. Uncertainty about the predictive value and reproducibility of any of the grading methods prompted a comparison of factors previously suggested as indicating the biologic behavior for cervical squamous carcinoma. One hundred ninety‐five women, who were enrolled in a Gynecologic Oncology Group treatment protocol of Stage IB squamous carcinoma of the cervix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(87 citation statements)
references
References 33 publications
2
82
1
2
Order By: Relevance
“…Increasing tumor size and increasing depth of stromal invasion correlated most strongly with LN metastasis and a shorter disease-free survival in previous studies of patients with FIGO stage 1B. 3,13 The accuracy and sensitivity rates with MRI for detecting LN metastasis from cervical cancer are between 76 to 100% and 36 to 71%, respectively. 14,15 However, the limitation of MRI is that it is not possible to differentiate metastatic LN from non-metastatic LN hyperplasia of similar size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing tumor size and increasing depth of stromal invasion correlated most strongly with LN metastasis and a shorter disease-free survival in previous studies of patients with FIGO stage 1B. 3,13 The accuracy and sensitivity rates with MRI for detecting LN metastasis from cervical cancer are between 76 to 100% and 36 to 71%, respectively. 14,15 However, the limitation of MRI is that it is not possible to differentiate metastatic LN from non-metastatic LN hyperplasia of similar size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…Since some pathologic parameters are related to patients' prognosis, these parameters affect the plan of further treatment. [4][5][6] This means that pathologic findings of surgical specimens are important for the management of patients with cervical cancer. However, clinicians should consider preoperative diagnosis, because the stage of cervical cancer is clinically determined and clinicians can get much information related with prognosis from preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…However, postoperative adjuvant therapy should be considered if pathologic findings demonstrate risk factors including lymph node metastases, deep cervical invasion, positive resection margin, parametrial invasion and bulkiness of tumor. [2][3][4] Among them, parametrial invasion and tumor size are evaluated by preoperative pelvic examination.…”
Section: Introductionmentioning
confidence: 99%
“…These include: volume and grade of tumor, histologic type, lymphatic spread, and vascular invasion. In a large surgicopathologic staging study of patients with clinical stage IB disease reported by the Gynecologic Oncology Group, the factors that predicted most prominently for lymph node metastases and a decrease in disease-free survival were capillarylymphatic space involvement by tumor, increasing tumor size, and increasing depth of stromal invasion, with the latter being most important and reproducible (2,3). In a study of 1.028 patients treated with radical surgery, survival rates correlated more consistently with tumor volume (as determined by precise volumetry of the tumor) than clinical or histologic stage (4).The preoperative diagnosis of tumor geography may play an important role in management of cervical cancer.…”
mentioning
confidence: 89%